Investigating Individual Factors and Mental Health with Preference of Delivery Type in Women Referred to Qamar-E-Bani-Hashem Hospital in Khoy in 2014 - Soudabeh Niroomand (Journal of Global Pharma Technology, 2017)
Background The consent of the mother on the experience of giving birth has to a large extent with the decision she made about the type of her next delivery. Health-related beliefs or Health Locus of Control(HLC), are referring to the point that to what extent a person's health is under control of internal factors (self) or external factors (effective or influential individuals).  Method 380 patients admitted to the Khoy hospital, gave birth to their childes, were selected randomly in this descriptive study. The participants in this study were asked about their next preferred method of delivery, Social demographic questionnaire were made, and trust in doctors and health-related beliefs questionnaires were completed by the participants. Descriptive statistics (mean, standard deviation) and analytical (Spearman correlation coefficient test and regression) were used for data analysis.  Research findings Mean age of women was in the range of 10/5 ± 24/24. The results showed psychosocial factors in the area of trust between doctor and health-related beliefs, there was no statistically significant relationship with the preferred method of delivery. Also, individual variables such as age, spouse's education, and income prognostic factors were the preferred method of delivery. Conclusion There was no significant relationship between the preferred type of labor and the psychological factors in women. However, with the increase in women's education and their spouses, as well as the type of job and income preferences about method of delivery also changed. By adopting the results of this research can develop strategies to reduce caesarean sections and its complications.Keywords: Method of delivery, Cesarean, Psychological factors.